Preventive Diplomacy / Types and Characteristics - Future Vision - Muataz Abdulqader Mohammed, (QALAAI ZANIST JOURNAL, 2023)
Diplomacy is generally a concept of political representation of states and the conduct of their foreign affairs with other countries within the framework of practicing international relations such as treaty, agreements and negotiations. The concept of preventive diplomacy established in the report of former UN Secretary General Boutros Boutros-Ghali on the peace plan submitted to the Security Council on June 17, 1992, which aimed to prevent conflicts between the parties. The escalation of existing conflicts and their transformation into conflicts, and stop the spread of these conflicts when they occur. Therefore, the prevention of conflict is a proactive procedure according to pre-prepared plans and time, and in order to achieve the foregoing there must be several means taken by states and organizations to achieve this benefit and in their destruction are the legal and political means to resolve international tendencies and differences (mediation - good offices - investigation - arbitration - conciliation). Also, in order to achieve great success of these means, it depends on a set of mechanisms that help to detect conflicts and tension in order to determine whether states or international organizations are able to overcome it.